Nejrolingvističeskij podchod na nervom uroke RKI s akcentom na ustnoj praktike: v poiskach lingvodidaktiki načalʹnogo urovnja - Bondarenko, Maria (Didaktik slawischer Sprachen, 2025)
This article examines how the application of the Neurolinguistic Approach (NLA) in the first lessons of Russian as a foreign language (RFL) addresses common beginner-level challenges within the communicative-actional teaching paradigm and provides a solid methodological foundation for Beginner L2 Pedagogy. Originally developed in the late 1990s and early 2000s for French language instruction in intensive school programs in English-speaking Canada (Germain, 2018), the NLA has since been adapted for teaching different languages in diverse contexts. We present three instructional modules implemented in the first RFL lessons at the Université de Montréal. These modules serve as the basis for discussing the principles of NLA-based instructional design, its adaptation to RFL teaching, and theoretical foundation based on two neurolinguistic concepts. To highlight the advantages of the NLA in the first RFL lessons, we also compare it with the traditional PPP (Presentation-Practice-Production) model, particularly with the version developed within the Soviet-Russian Communicative-Actional approach (Passov & Kuzovleva, 2010). The article demonstrates that the NLA facilitates the development of oral proficiency from the very first RFL lesson — independently of students’ reading and writing skills and explicit grammatical knowledge — while simultaneously fostering them on the basis of oral competence.